Public journalism connecting with the community - Evelio B. Javier Foundation ([Manilan] Evelio B. Javier Foundation, 2001)
Documentary showcases public journalism initiatives among community journalists in various parts of the Philippines.
Narration in English with some interviews in Filipino.
Summary taken from container insert.
VHS
Also available in VCD format.
Keywords: Journalism, Rural -- Philippines; Mass media -- Moral and ethical aspects -- Philippines; Mass media and social service -- Philippines; Mass media in community development -- Philippines